Neural alterations in working memory of mild-moderate TBI: an fMRI study in Malaysia - Wen, Jia Chai; Abdul Hamid, Aini Ismafairus; Omar, Hazim; Abdul Rahman, Muhammad Riddha; Fitzrol, Diana Noma; Idris, Zamzuri; Ghani, Abdul Rahman Izaini; Wan Mohamad, Wan Nor Azlen; Mustafar, Faiz; Hanafi, Muhammad Hafiz; Kandasamy, Regunath; Abdullah, Mohd Zaid; et al. (John Wiley and Sons Inc, 2022)
Working memory (WM) encompasses crucial cognitive processes or abilities to retain and manipulate temporary information for immediate execution of complex cognitive tasks in daily functioning such as reasoning and decision-making. The WM of individuals sustaining traumatic brain injury (TBI) was commonly compromised, especially in the domain of WM. The current study investigated the brain responses of WM in a group of participants with mild-moderate TBI compared to their healthy counterparts employing functional magnetic resonance imaging. All consented participants (healthy: n = 26 and TBI: n = 15) performed two variations of the n-back WM task with four load conditions (0-, 1-, 2-, and 3-back). The respective within-group effects showed a right hemisphere-dominance activation and slower reaction in performance for the TBI group. Random-effects analysis revealed activation difference between the two groups in the right occipital lobe in the guided n-back with cues, and in the bilateral occipital lobe, superior parietal region, and cingulate cortices in the n-back without cues. The left middle frontal gyrus was implicated in the load-dependent processing of WM in both groups. Further group analysis identified that the notable activation changes in the frontal gyri and anterior cingulate cortex are according to low and high loads. Though relatively smaller in scale, this study was eminent as it clarified the neural alterations in WM in the mild-moderate TBI group compared to healthy controls. It confirmed the robustness of the phenomenon in TBI with the reproducibility of the results in a heterogeneous non-Western sample.